How Servant Leadership Promote Psychological Resilience for Engagement and Performance from Job Demands-Resources View - Alex Winarno; Silvy Sondari Gadzali; Daniel Kisahwan; Deni Hermana (Qubahan Academic Journal)
The purpose of the study is to examines the role of psychological resilience as a mediator in the relationship between servant leadership, work engagement, and academic performance, utilizing the Job Demands-Resources (JD-R) framework in higher education. This study employed a survey technique with a sample of 475 randomly selected lecturers—multivariate analysis using SEM analysis with the maximum likelihood estimation method. The findings underscore the significant positive impact of servant leadership servant leadership exerts a significant positive influence on psychological resilience (β = 0.268, p < 0.05), which, in turn, enhances work engagement (β = 0.345, p < 0.05) and performance (β = 0.090, p < 0.05). Furthermore, work engagement mediates the relationship between servant leadership and performance (indirect effect = 0.134, p < 0.05).  Psychological resilience mediates the relationship between servant leadership and work engagement (indirect effect = 0.055, p < 0.05).  work engagement mediates the relationship between psychological resilience and performance (indirect effect = 0.169, p < 0.05).  The model demonstrated a good fit (CFI = 0.96, TLI = 0.95, RMSEA = 0.034), validating the robustness of the proposed framework. Leaders who prioritize service-oriented leadership and demonstrate responsiveness to subordinates' psychological needs cultivate a resilient workforce, thereby fostering higher levels of engagement and organizational commitment. Furthermore, the study establishes work engagement as a mediating variable in the relationship between servant leadership and performance. These findings offer critical implications for higher education institutions, suggesting that adopting a servant leadership approach can serve as a strategic mechanism for enhancing faculty engagement, resilience, and overall performance. in higher education.